The impact of apical patency in the success of endodontic treatment of necrotic teeth with apical periodontitis: A brief review - Machado, Ricardo; Ferrari, Carlos Henrique [UNESP]; Back, Eduardo; Comparin, Daniel; Tomazinho, Luiz Fernando; Vansan, Luiz Pascoal (My University, 2016)
Accumulation of soft tissue or dentinal remnants in the apical region is a common event that can cause blockage of root canals. This event can be avoided if apical patency is performed during the root canal shaping procedures. However, there is no consensus on the role of apical patency in relation to the success of endodontic treatment of necrotic teeth with apical periodontitis. Therefore, the purpose of this paper was to conduct a brief review on the role of apical patency in guaranteeing the success of endodontic treatments of necrotic teeth with apical periodontitis considering two other key points; the root canal anatomy and microbiology.
Keywords: Apical Patency; Endodontic Success; Periradicular Disease; Root Canal Therapy